Optimal Anchor at the Uppermost Instrumented Vertebra in Long Fusion From the Pelvis to the Lower Thoracic Spine in Elderly Patients With Degenerative Spinal Deformity: Hook Versus Pedicle Screw. Issue 1 (February 2022) - Tsutsui, Shunji; Hashizume, Hiroshi; Yukawa, Yasutsugu; Minamide, Akihito; Nakagawa, Yukihiro; Iwasaki, Hiroshi; Takami, Masanari; Yamada, Hiroshi
Abstract : Study Design: This was a retrospective cohort study. Objective: The objective of this study was to compare pedicle screws (PSs) and transverse process hooks (TPHs) as anchors at the uppermost instrumented vertebra (UIV) in the lower thoracic spine in elderly patients with adult spinal deformity. Summary of Background Data: Less-rigid fixation using hooks at the UIV are thought to best prevent proximal junctional kyphosis (PJK) in long spinal fusion surgery. Although adult spinal deformity is commonly treated via spinal fusion from the pelvis to the lower thoracic spine, few studies have focused on UIV anchors in the lower thoracic spine. Materials and Methods: We retrospectively reviewed 53 patients aged 65 years and above who underwent spinal fusion from the pelvis to T9 or T10, with a minimum follow-up of 1 year. Radiographic outcomes including the incidence of PJK and implant failure were compared between 28 patients with TPHs and 25 patients PSs at the UIV. Results: The TPH and PS groups had similar radiographic values for pelvic incidence-lumbar lordosis (preoperative: 42.8 vs. 49.0 degrees, postoperative: 9.9 vs. 7.3 degrees) and the sagittal vertical axis (preoperative: 109.3 vs. 106.8 mm; postoperative: 21.9 vs. 11.2 mm). However, the incidence of PJK was significantly higher in the TPH group (35.7%) than that in the PS group (8.0%) at the 1-year follow-up ( P =0.012). PJK in the TPH group was associated with UIV or UIV±1 fracture accompanied by posterior dislodgement of the TPH. Conclusion: Rigid fixation using PSs at the UIV in the lower thoracic spine produced better radiographic outcomes than did TPHs in elderly patients undergoing spinopelvic fusion. Level of Evidence: Level III.